HLA class I and II alleles in susceptibility to ankylosing spondylitis. Issue 1 (19th October 2018) - Reveille, John D; Zhou, Xiaodong; Lee, MinJae; Weisman, Michael H; Yi, Lin; Gensler, Lianne S; Zou, Hejian; Ward, Michael M; Ishimori, Mariko L; Learch, Thomas J; He, Dongyi; Rahbar, Mohammad H; et al.
Abstract : Objective: To examine associations of HLA class I and class II alleles with ankylosing spondylitis (AS) in three cohorts of patients of European, Asian and African ancestry. Methods: HLA-A, HLA-B, HLA-C, HLA-DRB1, HLA-DQB1 and HLA-DPB1 alleles were genotyped in 1948 unrelated white and 67 African-American patients with AS from the Prospective Study of Outcomes in Ankylosing Spondylitis cohort, the North American Spondylitis Consortium and Australo-Anglo-American Spondyloarthritis Consortium, 990 white and 245 African-American Controls and HLA-B alleles in 442 Han Chinese patients with AS and 346 controls from Shanghai and Gansu, China. In addition to the case:control analyses, HLA-B*27 -negative patients with AS were analysed separately, and logistic regression and 'relative predispositional effects' (RPE) analyses were carried out to control for the major effect of HLA-B*27 on disease susceptibility. Results: Although numerous associations were seen between HLA alleles and AS in whites, among HLA-B*27-negative patients with AS, positive associations were seen with HLA-A*29, B*38, B*49, B*52, DRB1*11 and DPB1*03:01 and negative associations with HLA-B*07, HLA-B*57, HLA-DRB1*15:01, HLA-DQB1*02:01 and HLA -DQB1*06:02 . Additional associations with HLA-B*14 and B*40 (B60) were observed via RPE analysis, which excludes the HLA-B*27 alleles. The increased frequency of HLA-B*40:01 and decreased frequency of HLA-B*07 was also seen in Han Chinese and African-Americans with AS. HLA-B*08 was decreased in whites with acute anterior uveitis. Conclusions: These data, analysing the largest number of patients with AS examined to date in three ethnic groups, confirm that other HLA class I and II alleles other than HLA-B*27 to be operative in AS predisposition.